Quoting in parliamentary question time: exploring recent change - Reber, Elisabeth (Cambridge University Press, 2021)
Why do recordings of speakers engaging in reported speech at British Prime Minister's Questions from the 1970s-80s sound so distant to us? This cutting-edge study explores how the practices of quoting have changed at parliamentary question time in light of changing conventions and an evolving media landscape. Comparing data from authentic audio and video recordings from 1978 to 1988 and from 2003 to 2013, it provides evidence for qualitative and quantitative changes at the micro level (e.g., grammaticalisation processes in the reporting clause) and in more global structures (e.g., rhetorical patterns, and activities). These analytic findings contribute to the theoretical modelling of evidentiality in English, our understanding of constructions, interaction, and change, and of PMQs as an evolving community of practice. One of the first large-scale studies of recent change in an interactional genre of English, this ground-breaking monograph offers a framework for a diachronic interactional (socio-) linguistic research programme.
Title from publisher's bibliographic system (viewed on 27 Aug 2021)
Keywords: Geschichte 1978-2013; Sprachwandel; Zitat; Politische Rede; Englisch